Field notes contributed by Raymond L. Cummins, February 27, 1983 - Cummins, Raymond L.et al (1983)
Winter report of birds contributed by Raymond L. Cummins, February 27, 1983. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1982-1983. Epson - sheet feed